Indonesian Sharia Fintech Peer to Peer (P2P) Lending Business Model - Fikar, One Yusril; Rahadian, Dadan; Krisnawati, Astrie (Jurnal Ekonomi dan Bisnis Digital, 2024)
This study examines the business model of sharia P2P lending fintech in Indonesia by utilizing the Business Model Canvas (BMC) and Value Design Model (VDM) frameworks. The research aims to provide insights into how sharia fintech companies in Indonesia are structured, focusing on key elements such as value propositions, revenue streams, and customer segments. The study involves three sharia P2P lending companies—ES, PS, and AS—and analyzes their business models through qualitative methods. Key findings highlight the importance of sharia-compliant, transparent, and flexible financing to build customer trust, alongside partnerships with sharia banks, tech providers, and communities. The sector’s growth is driven by targeting customers with stable incomes and familiarity with sharia principles, but challenges remain in financial literacy and regulatory support. Recommendations include product innovation (e.g., wakaf or zakat-based financing), expanding digital channels, and improving operational efficiency to ensure sustainable growth.